2017
DOI: 10.1515/bmc-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and the gut-brain axis: is there a role for melatonin?

Abstract: The benefits of breastfeeding over formula feed are widely appreciated. However, for many mothers breastfeeding is not possible, highlighting the need for a significant improvement in the contents of formula feed. In this article, the overlooked role of melatonin and the melatonergic pathways in breast milk and in the regulation of wider breast milk components are reviewed. There is a growing appreciation that the benefits of breastfeeding are mediated by its effects in the infant gut, with consequences for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 111 publications
0
23
0
4
Order By: Relevance
“…Such signaling molecules include catecholamines, serotonin, gamma aminobutyric acid (GABA), dopamine, acetylcholine, a-MSH, norepinephrine, and melatonin, all of which can leave the gut lumen. 109,114,115 The microbiota also influences the production of metabolites by the enteroendocrine cells. For example, 90% of the body's serotonin is produced by enteroendocrine cells in the gut, 116 which has a major influence on mood and cognition.…”
Section: Human Microbiomementioning
confidence: 99%
“…Such signaling molecules include catecholamines, serotonin, gamma aminobutyric acid (GABA), dopamine, acetylcholine, a-MSH, norepinephrine, and melatonin, all of which can leave the gut lumen. 109,114,115 The microbiota also influences the production of metabolites by the enteroendocrine cells. For example, 90% of the body's serotonin is produced by enteroendocrine cells in the gut, 116 which has a major influence on mood and cognition.…”
Section: Human Microbiomementioning
confidence: 99%
“…The development and maturation factors will promote, as their name implies, the maturation, differentiation and development of the local immune system, known as the gut‐associated lymphoid tissue (GALT), and the systemic immune system. Furthermore, it will also promote the development of immune tolerance …”
Section: Breast Milk and Immune System Modulationmentioning
confidence: 99%
“…Formula-feeding can therefore contribute to the desynchronization of metabolic processes, imbalances in energy exchange, and excessive weight gain [69][70][71]. Such data has contributed towards a drive to have a nighttime formula feed that contains melatonin, which may be important for the high percentage of mothers who do not exclusively breastfeed [72], especially as this may be important to the development of the gut-brain axis [73]. This is supported by a recent retrospective study, where breast-feeding by nonobese mothers for 10-12 months showed good infant outcomes, including measures of weight, length, and colic.…”
Section: Melatonin Metabolism and Mother-placenta-fetus Interfacementioning
confidence: 99%